Педагогика сотрудничества как образовательная концепция XXI века: концепция формирования инклюзивной готовности педагогов - Муминова, Л. Р.; Якубжанова, Д. Б.
The paper presents the basic ideas of the concept of forming an inclusive readiness of the future pedagoguesdefectologists. The effectiveness of inclusive education is seen as providing equal access to education for all students, given the diversity of special educational needs and individual capabilities, which provides psychological and pedagogical formed (inclusive) readiness of teachers to intersectoral cooperation with all stakeholders inclusive educational environment. Inclusive willingness of a pedagogue is defined as a complex integral subjective quality of a person, which is revealed through meaningful complex competencies and determines the possibility of a creative professional and pedagogical activities in the real world․
Keywords: Эффективные модели образования